Britain, America and Rearmament in the 1930s - Price, C. author. aut Link
XVI, 228 p.
Keywords: This book is the first to challenge current orthodoxy that Chamberlain's appeasement policy before World War Two was justified by Britain's inability to pay for rearmament. The book shows that British war potential was actually massive, with a solid foundation in the existing Imperial economy. Using previously unconsidered and recently declassified documents from British and American archives the author demonstrates that the deliberate and political rejection of rearmament in the hope of eventual American support proved catastrophic for Britain.